2015
DOI: 10.1556/066.2015.44.0017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of antioxidant activity evaluation of green and roast C. Arabica and C. Robusta coffee beans

Abstract: Coffee beans contain a large amount of antioxidants, which are subjected to various changes during roasting. In this study, antioxidant potential of raw and roasted to different degree (light, medium, dark) C. arabica and C. robusta coffee beans was evaluated by the four antioxidant assay methods, TPC, FRAP, TEAC, and DPPH˙.The obtained results revealed signifi cant differences between the coffee types, roasting degree, and antioxidant activity assessment methods. FRAP and TPC appeared to be the most appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 15 publications
2
27
1
4
Order By: Relevance
“…The antioxidant capacity of each sample was evaluated using the •DPPH, ABTS•+, FRAP and BCBA assays (Table ). There is a variety of in vitro methods to assess the antioxidant capacity of food, plant extracts and other substances; where most of them are based on single electron (SET) and hydrogen atom (HAT) transfer reactions (Pokorná et al ., ). Their response depends on a range of factors, such as pH, lipophilic and/or hydrophilic compounds, among others.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The antioxidant capacity of each sample was evaluated using the •DPPH, ABTS•+, FRAP and BCBA assays (Table ). There is a variety of in vitro methods to assess the antioxidant capacity of food, plant extracts and other substances; where most of them are based on single electron (SET) and hydrogen atom (HAT) transfer reactions (Pokorná et al ., ). Their response depends on a range of factors, such as pH, lipophilic and/or hydrophilic compounds, among others.…”
Section: Resultsmentioning
confidence: 97%
“…Their response depends on a range of factors, such as pH, lipophilic and/or hydrophilic compounds, among others. Hence, although the principle of each antioxidant method is similar, it is indicated to employ more than one technique in order to evaluate the antioxidant capacity of a matrix, especially when such phytochemically complex matrices as coffee beans products are being studied (Pokorná et al ., ). According to the assays, GCC showed an increased antioxidant capacity compared with the respective GCB (Table ), except for BCBA.…”
Section: Resultsmentioning
confidence: 97%
“…Studies have shown that no single test can estimate accurately the antioxidant activity in a sample, mainly because standardized methods should evaluate its availability against various oxygen reactive species and/or nitrogen reactive species, such as superoxide anion, hydroxyl (OH) and peroxynitrite, so this requires specific methods for specific radical sources. Thus, the use of different methods is necessary in antioxidant activity measurement and together these techniques could draw a reliable profile of the antioxidant content in a food matrix [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activities of the extracts against DPPH radical were similar to each other and the results were not correlated with total phenolic content of the extracts. Previous studies concluded that antioxidant activity depends on the roasting time and coffee type, and the selected method is also a significant factor (Pokorna et al 2015;Priftis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%